Low-voltage ride-through control strategy for a grid-connected energy storage system - Bak, Yeongsu; Lee, June Seok; Lee, Kyo Beum (Applied Sciences (Switzerland), 2018)
This paper presents a low-voltage ride-through (LVRT) control strategy for grid-connected energy storage systems (ESSs). In the past, researchers have investigated the LVRT control strategies to apply them to wind power generation (WPG) and solar energy generation (SEG) systems. Regardless of the energy source, the main purpose of the LVRT control strategies is to inject reactive power into the grid depending on the grid-code regulations using the grid-side inverter; the proposed LVRT control strategy for grid-connected ESSs also has the same purpose. However, unlike the WPG and SEG systems having unidirectional power flow, grid-connected ESSs have a bidirectional power flow. Therefore, the charging condition of the grid-connected ESSs should be considered for the LVRT control strategy. The proposed LVRT control strategy for grid-connected ESSs determines the injection quantity of the active and reactive currents, and the strategy depends on the voltage drop ratio of the three-phase grid. Additionally, in this paper, we analyzed the variations of the point of common coupling (PCC) voltage depending on the phase of the reactive current during the charging and discharging conditions. The validity of the proposed LVRT control strategy is verified and the variations of the PCC voltage of the grid-connected ESS are analyzed by simulation and experimental results.
Keywords: Energy storage system; Grid-connected; Low voltage ride through; Solar energy generation system; Wind power generation system